The relationship between the lower-body muscular profile and swimming start performance - Garcia-Ramos, A.; Tomazin, K.; Feriche, B.; Strojnik, V.; De La Fuente, B.; Arguelles-Cienfuegos, J.; Strumbelj, B.; Stirn, I. (Journal of Human Kinetics, 2016)
This study aimed to examine the correlation of different dry land strength and power tests with swimming start performance. Twenty international level female swimmers (age 15.3 ± 1.6 years, FINA point score 709.6 ± 71.1) performed the track freestyle start. Additionally, dry land tests were conducted: a) squat (SJ) and countermovement jumps (CMJ), b) squat jumps with additional resistance equivalent to 25, 50, 75 and 100% of swimmers` body weight [BW]), and c) leg extension and leg flexion maximal voluntary isometric contractions. Correlations between dry land tests and start times at 5, 10 and 15 m were quantified through Pearson`s linear correlation coefficients (r). The peak bar velocity reached during the jumps with additional resistance was the variable most correlated to swimming start performance (r = -0.57 to -0.66 at 25%BW; r = -0.57 to -0.72 at 50%BW; r = -0.59 to -0.68 at 75%BW; r = -0.50 to - 0.64 at 100%BW). A few significant correlations between the parameters of the SJ and the CMJ with times of 5 and 10 m were found, and none with the isometric variables. The peak velocity reached during jumps with external loads relative to BW was found a good indicator of swimming start performance.